Carotid Endarterectomy: Current Concepts and Practice Patterns - Saha, Sibu P. (Int J Angiol, 2015)
Background Stroke is the number one cause of disability and third leading cause of death among adults in the United States. A major cause of stroke is carotid artery stenosis (CAS) caused by atherosclerotic plaques. Randomized trials have varying results regarding the equivalence and perioperative complication rates of stents versus carotid endarterectomy (CEA) in the management of CAS. Objectives We review the evidence for the current management of CAS and describe the current concepts and practice patterns of CEA. Methods A literature search was conducted using PubMed to identify relevant studies regarding CEA and stenting for the management of CAS. Results The introduction of CAS has led to a decrease in the percentage of CEA and an increase in the number of CAS procedures performed in the context of all revascularization procedures. However, the efficacy of stents in patients with symptomatic CAS remains unclear because of varying results among randomized trials, but the perioperative complication rates exceed those found after CEA. Conclusions Vascular surgeons are uniquely positioned to treat carotid artery disease through medical therapy, CEA, and stenting. Although data from randomized trials differ, it is important for surgeons to make clinical decisions based on the patient. We believe that CAS can be adopted with low complication rate in a selected subgroup of patients, but CEA should remain the standard of care. This current evidence should be incorporated into practice of the modern vascular surgeon.